Controllability of semilinear stochastic systems in Hilbert spaces - Mahmudov, NI (Academic Press Inc Elsevier Science, 2003)
We study the weak approximate and complete controllability properties of semilinear stochastic systems assuming controllability of the associated linear systems. The results are obtained by using the Banach fixed point theorem. Applications to stochastic heat equation are given. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: weak approximate controllability; complete controllability; stochastic differential equation